1999
DOI: 10.1161/01.cir.100.9.933
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of Myocardial Expression of Inducible Nitric Oxide Synthase Influences the Clinical Course of Human Immunodeficiency Virus-Associated Cardiomyopathy

Abstract: Cytokine activation seems to play a significant pathogenetic role in both HIV-DCM and IDCM. In HIV-DCM patients, the state of immunodeficiency may favor the selection of viral variants of increased pathogenicity, influencing the clinical course of cardiomyopathy by enhancement of the inflammatory process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
66
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 27 publications
2
66
0
1
Order By: Relevance
“…Myocardial dendritic cells may play a role in the interaction between HIV-1 and the cardiac myo cyte and in the activation of cytotoxic cytokines 17 . Dendritic cells can initiate the primary immunologic response and present the antigen to T-lymphocytes.…”
Section: Myocardial Cytokine Expressionmentioning
confidence: 99%
See 4 more Smart Citations
“…Myocardial dendritic cells may play a role in the interaction between HIV-1 and the cardiac myo cyte and in the activation of cytotoxic cytokines 17 . Dendritic cells can initiate the primary immunologic response and present the antigen to T-lymphocytes.…”
Section: Myocardial Cytokine Expressionmentioning
confidence: 99%
“…TNF-alpha produces a negative ino tropic effect by altering intracellular calcium ho meostasis, possibly by inducing nitric oxide (NO) synthesis, which also reduces myocyte contractil ity. Kan et al demonstrated that HIV gp120 enhances NO production by cardiac myocytes through p38 MAP kinase-mediated NK-kB activation 19 .Myocarditis and dilated cardiomyopathy are associated with markedly elevated cytokine pro duction, but the elevations may be highly local ized within the myocardium, making peripheral cytokine levels uninformative 20 . When myocar dial biopsies from patients with HIV-associated cardiomyopathy are compared to samples from patients with idiopathic dilated cardiomyopathy, the former stain more intensely for both TNFalpha and inducible nitric oxide synthase (iNOS).…”
Section: Myocardial Cytokine Expressionmentioning
confidence: 99%
See 3 more Smart Citations